The assessment of online health videos for surgery in Crohn's disease. (2nd July 2018) - Marshall, J. H.; Baker, D. M.; Lee, M. J.; Jones, G. L.; Lobo, A. J.; Brown, S. R.
Abstract: Aim: YouTube™ is an open‐access, nonpeer‐reviewed video‐hosting site and is used as a source of publicly available healthcare information. This study aimed to assess the thematic content of the most viewed videos relating to surgery and Crohn's disease and to explore the viewer interactions with these videos. Method: A search of YouTube™ was carried out using one search string. The 50 most viewed videos were identified and categorized by source and content themes and assessed for viewer interactions. Video comments were used to describe the usefulness of the video content to viewers. Results: The majority of videos were uploaded by patients ( n = 21).The remainder were uploaded by individual healthcare professionals ( n = 9), hospital/speciality associations ( n = 18) and industry ( n = 2). The median number of likes for patient videos was significantly higher than for hospital/speciality association videos ( P < 0.001). Patient videos received more comments praising the video content ( n = 27) and more comments asking for further information ( n = 14). The median number of likes for 'experience of surgery' ( P < 0.001) and 'experience of disease' ( P = 0.0015) themed videos were significantly higher than for 'disease management' themed videos. Conclusion: Crohn's disease patients use YouTube™ as a surgical information source. The content of patient‐sourced videos focused on surgical and disease experience, suggesting that these themes are important to patients. Current patient developed videos provide limited information, as reflected by viewers requesting further information. Storytelling patient‐centred videos combined with clinical evidence may be a good model for future videos.